Kondisi Sosial, Ekonomi , Kualitas Air dan Status Mutu Air Sungai Sosa - Alfi Syahrin; Budijono Budijono; Yuliati Yuliati (Jurnal Zona, 2024)
The Sosa River in Padang Lawas, North Sumatra, is facing pollution from domestic waste and industrial activities. Its water quality has declined, with a Water Quality Index of 58.75% in 2022, indicating a moderate condition. The community directly disposes of waste into the river, exacerbating the ecosystem's deterioration. This study aims to evaluate and analyze the water quality conditions of the Sosa River and the social and economic activities of the Padang Lawas community, determine the pollution load and water quality status. he existing condition of the Sosa River water quality still has several parameters that exceed the quality standards in accordance with applicable regulations. The Sosa River water quality status at the research location is classified as meeting quality standards to moderately polluted. The location that has a moderate pollutant index is point 2 of the Sosa River tributary  (representing the outfall of the Sosa River tributary in Aliaga Village). while other research locations are classified as lightly polluted and some meet quality standards.